Description and outcome of a cohort of 8 patients with WHIM syndrome from the French Severe Chronic Neutropenia Registry - Beaussant Cohen Sarah; Fenneteau Odile; Plouvier Emmanuel; Rohrlich Pierre-Simon; Daltroff Gerard; Plantier Isabelle; Dupuy Alain; Kerob Delphine; Beaupain Blandine; Bordigoni Pierre; Fouyssac Fanny; Delezoide Anne-Lise; et al. (Orphanet Journal of Rare Diseases, 2012)
Abstract Background WHIM syndrome (WS), a rare congenital neutropenia due to mutations of the CXCR4 chemokine receptor, is associated with Human Papillomavirus (HPV)-induced Warts, Hypogammaglobulinemia, bacterial Infections and Myelokathexis. The long term follow up of eight patients highlights the clinical heterogeneity of this disease as well as the main therapeutic approaches and remaining challenges in the light of the recent development of new CXCR4 inhibitors. Objective This study aims to describe the natural history of WS based on a French cohort of 8 patients. Methods We have reviewed the clinical, biological and immunological features of patients with WS enrolled into the French Severe Chronic Neutropenia Registry. Results We identified four pedigrees with WS comprised of eight patients and one foetus. Estimated incidence for WS was of 0.23 per million births. Median age at the last visit was 29 years. Three pedigrees encompassing seven patients and the fetus displayed autosomal dominant heterozygous mutations of the CXCR4 gene, while one patient presented a wild-type CXCR4 gene. Two subjects exhibited congenital conotruncal heart malformations. In addition to neutropenia and myelokathexis, all patients presented deep monocytopenia and lymphopenia. Seven patients presented repeated bacterial Ears Nose Throat as well as severe bacterial infections that were curable with antibiotics. Four patients with late onset prophylaxis developed chronic obstructive pulmonary disease (COPD). Two patients reported atypical mycobacteria infections which in one case may have been responsible for one patient’s death due to liver failure at the age of 40.6 years. HPV-related disease manifested in five subjects and progressed as invasive vulvar carcinoma with a fatal course in one patient at the age of 39.5 years. In addition, two patients developed T cell lymphoma skin cancer and basal cell carcinoma at the age of 38 and 65 years. Conclusions Continuous prophylactic anti-infective measures, when started in early childhood, seem to effectively prevent further bacterial infections and the consequent development of COPD. Long-term follow up is needed to evaluate the effect of early anti-HPV targeted prophylaxis on the development of skin and genital warts.